Psikoedukasi Menjaga Kesehatan Mental untuk Mempersiapkan Orientasi Karir di Masa Depan Pada Mahasiswa: Psikoedukasi Menjaga Kesehatan Mental untuk Mempersiapkan Orientasi Karir di Masa Depan pada Mahasiswa - Dewi Anggraini; Amalia Juniarly; Rachmawati (Universitas Muhammadiyah Palembang, 2025)
The focus of this activity is psychoeducation aimed at sustaining mental health in preparation for students' future job orientation. The progression of contemporary society aligns with advancements in technology, resulting in the creation of increasingly competitive employment opportunities. Students, as future job seekers, have significant demands for career success and maintain high expectations of their parents. This is a significant burden and responsibility for a student to bear. According to developmental theory, individuals in the early adult stage are characterized as students, who are tasked with the responsibility of independently determining their future career paths. As a student, formulating a career plan will be associated with the educational process undertaken, particularly at the university level. The objective is to facilitate the development of individuals following the phases of life that they will encounter in the future through the educational process. The stages of development in students are in late adolescence and early adulthood when viewed from the developmental spectrum. During this stage, the individual's mental condition is unstable, and they may experience conflicts, demands, and mood swings. This condition can impact the academic journey of students, particularly through the experience of depression stemming from a decline in academic performance. Therefore, it is essential to recognize that the mental health of students plays a crucial role in anticipating potential negative impacts on students, educational institutions, families, the surrounding environment, and future career paths. Mental health is a critical issue that requires focused attention.